Overview of Mental Health of Pregnant Women in Yogyakarta - Esitra Herfanda; Nuli Nuryanti Zulala (Jurnal Kebidanan, 2023)
PSD (pregnancy-specific distress) is a distress condition regarding physical symptoms during pregnancy, changes in body shape, changes in interpersonal relationships with other people, childbirth, baby's health, how to care for a newborn, and the risks of medical treatment being carried out. higher PSD, the risk of preterm birth and LBW increases. The mental health of pregnant women in Yogyakarta is in the normal category. Health workers and family support play an important role in reducing anxiety to depression in pregnancy.